PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP TINGKAT PEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN KIMIA - Nila Purnama Sari (Universitas Muhammadiyah Semarang, 2017)
MAN 01 Semarang is a high school with a good achievement in the field of academic and non academic. Academic achievement is not separated from the four competence of teachers of professional competence, social competence, personality competence, and pedagogic competence. This study aims to determine the influence of pedagogic competence of teachers on the level of understanding of student learning on chemistry subjects. The type of research used is qualitative and quantitative research with data collection method questionnaire, interview, and observation. The subjects of this study are the students of class X IPA2 and class X IPA 4. The variables used are independent variables are teacher pedagogic competence and the dependent variable is the level of understanding of student learning on chemistry subjects. The results of this study show the pedagogical competence of teachers affect the understanding of student learning on chemistry subjects in MAN 01 Semarang with the average score is 3.066 is in good condition and relevant to previous research-penelian. Keywords: teacher pedagogic competence, student learning comprehension